Development paradigms : Indian development experiences: essays in honour of professor S. K. Bose - Sinha, R. K.; Das, D. K.; Sinha, A. K. edt; Bose, S. K. (New Delhi : Deep & Deep Pubs., 1992)
Essays in honour of prof. S. K. Bose, b. 1921, a former vice-chancellor of the Bihar University
Includes bibliographical references and index
Keywords: Economic development; India -- Economic policy -- 1947-; India -- Economic conditions -- 1947-; Developing countries -- Economic policy